Cardiac functions and pericardial thickness changes in familial Mediterranean fever patients - Yigit, Yasemin Demir; Karatoprak, oezlem Karakus; Ay, Elif Guzelsoy; Karabulut, Muhammed; Yilmaz, Erdal; Gurgoze, Metin Kaya (Springernature, 2024)
Background The goal of the study is to ascertain how the pericardium and heart functions alter in patients with familial Mediterranean fever (FMF) both during the acute phase and the period of subclinical inflammation. Methods During the study, 99 patients diagnosed with FMF (35 of whom were in an FMF attack period) were recruited to this study, and 24 completely healthy children in the same age group-who did not have FMF and had not any cardiac condition that applied to visit the pediatric cardiology outpatient clinic for routine follow-up-were included as the control group. Results In patients with FMF, there was no discernible relationship between genetic abnormalities and pericardial thickness (p > 0.05). A significant difference was not observed in the diastolic and systolic cardiac function values between the control group and the FMF patients, with the exception of the parameters related to ejection time (ET), contraction time (IVCT), and relaxation time (IVRT). It was observed that pericardial thickness was greater in FMF patients than in study participants who did not have FMF, and this difference is statistically significant (p < 0.05). Conclusions It was determined that the effects of cardiac inflammation continued in children with FMF, even if they were asymptomatic. Therefore, it should be part of the follow-ups.
Keywords: Children; FMF; Cardiac functions; Pericardial involvement